Bridging the Gap: Tailoring Waste Management Strategies for Sustainable Outcomes in Developing Countries - Mochammad, Fadhil Hayan (Golden Ratio of Mapping Idea and Literature Format, 2024)
This research aims to explore the effectiveness of tailored waste management strategies in developing countries, drawing lessons from both successful models in similar economies and advanced practices in developed countries. By examining case studies like Teocelo, Veracruz in Mexico, and analyzing the ambitious waste management targets of the European Union, this study proposes a hybrid approach that integrates community-based strategies, formal and informal sector collaboration, and customized regional policies. Through qualitative and quantitative analysis, this research seeks to test propositions related to the adaptation of waste management strategies, the role of community engagement, and the potential for developing countries to leapfrog to sustainable waste management practices by learning from developed nations. The goal is to identify scalable and sustainable waste management practices that can address the unique challenges faced by developing countries, while also contributing to global environmental goals. This research contributes to the literature by offering a nuanced understanding of how developing countries can navigate the complexities of waste management by adopting, adapting, and innovating practices suited to their socio-economic and environmental contexts. By bridging the gap between the advanced waste management systems of developed countries and the emerging practices in developing nations, this study aims to provide actionable insights for policymakers, environmental managers, and community leaders working towards sustainable waste management solutions.